Perubahan Pemanfaatan Lahan Perumahan Ke Perkantoran: Implikasinya Terhadap Pengendalian Pemanfaatan Ruang Kota (Studi Kasus: Wilayah Pengembangan Cibeunying Kota Bandung) - Iwan Kustiwan; Melani Anugrahani (The Institute for Research and Community Services, Institut Teknologi Bandung, 2000)
Change in urban land use is a phenomenon that often occurs along with the development of urban area. At the city center and fringe area, competition among urban activities has caused changes in land use from residential use to non-residential use (trade and services/commercial). The current trend is the development of office activities (government and private) that has reached residential area. The change in land use is often inconsistent with the city spatial plan and has caused negative impacts physical, environment, and social. On one side, this problem reflects the weakness of land use control in urban area in permit issuance, monitoring, and law and order. On the other side, the formulation of the spatial plan may not sensitive to the rapid development of urban economics activities